Kualitas Pelayanan Publik Pemerintah Daerah (Kasus Pelayanan IMB pada KPTSA Kabupaten Bone) - Rabina Yunus (Otoritas : Jurnal Ilmu Pemerintahan, 2011)
Measuring the quality of public services in the Building Permit in the one-stop services office of Bone Regency, using indicators of the ability of the apparatus, system services and influential factor in the service of Building permit. The data was collected through interviews, observation and documentation, as a way to know the description of the organizational structure, education and training, ability to work completion on schedule, the convenience in obtaining services, clarity of information, security and protection services to consumers in the Office of One-Stop Services (KPTSA) of Bone Regency. The factors that affect the public service of Building Permit (IMB), among others; timeliness, ease of filing, the accuracy of service, the cost of service. Factor is a barometer of the consumer or the use of the service, so whether or not the services provided by the government back to the things mentioned above. In the public service should further develop the quality of human resources and democratization, leadership model must shift from power to the approach of expertise (from macho to maestro) and democratic in spirit, close to the subordinates and apply humanistic model of bureaucracy is putting a human in its proportions.Mengukur kualitas pelayanan publik dalam Izin Bangunan di kantor pelayanan satu atap Kabupaten Bone, dengan menggunakan indikator kemampuan aparatur, sistem layanan dan faktor yang berpengaruh dalam pelayanan Membangun izin. Data dikumpulkan melalui wawancara, observasi dan dokumentasi, sebagai cara untuk mengetahui gambaran struktur organisasi, pendidikan dan pelatihan, kemampuan untuk bekerja selesai sesuai jadwal, kenyamanan dalam memperoleh pelayanan, kejelasan layanan informasi, keamanan dan perlindungan kepada konsumen di Kantor Pelayanan Satu Atap (KPTSA) Kabupaten Bone. Faktor- faktor yang mempengaruhi pelayanan publik Izin Mendirikan Bangunan (IMB), antara lain; ketepatan waktu, kemudahan pengajuan, akurasi pelayanan, biaya pelayanan. Faktor adalah barometer konsumen atau penggunaan layanan, sehingga apakah layanan yang diberikan oleh pemerintah kembali ke hal-hal tersebut di atas. Dalam layanan publik lebih lanjut harus mengembangkan kualitas sumber daya manusia dan demokratisasi, model kepemimpinan harus bergeser dari kekuasaan ke pendekatan keahlian (dari macho untuk maestro) dan berjiwa demokratis, dekat dengan bawahan dan menerapkan model birokrasi humanistik adalah meletakkan manusia dalam proporsinya.